Recombinant XBB.1.5 boosters induce robust neutralization against KP.2- and KP.3-included JN.1 sublineages - Jingyun Yang; Xuemei He; Huashan Shi; Cai He; Hong Lei; Heng He; Li Yang; Wei Wang; Guobo Shen; Jinliang Yang; Zhiwei Zhao; Xiangrong Song; et al. (Signal Transduction and Targeted Therapy)
Abstract The newly emerged variants of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) demonstrate resistance to present therapeutic antibodies as well as the capability to evade vaccination-elicited antibodies. JN.1 sublineages were demonstrated as one of the most immune-evasive variants, showing higher neutralization resistance compared to XBB.1.5. In this study, serum samples were collected from adult participants including those who had gone through the BA.5/BF.7, EG.5/HK.3 and XBB/JN.1 infection waves, characterized by different infection and vaccination histories. We evaluated the neutralization in these serum samples against pseudoviruses of Omicron lineages. We further investigated humoral immune response of recombinant XBB vaccines against Omicron variants and estimated the neutralization resistance of JN.1 sublineages, including KP.2 and KP.3. Our results showed that sera from previous circulating Omicron subvariant breakthrough infections exhibited low neutralization against pseudoviruses of Omicron lineages. The GMTs of 50% neutralization against all tested pseudoviruses were significantly elevated in sera from individuals who received WSK-V102C or WSK-V102D boosters. Importantly, the GMTs of 50% neutralization in serum samples from individuals 4 months after a WSK-V102D booster against XBB.1.5, JN.1, JN.1.13, KP.2 and KP.3 pseudoviruses were 3479, 1684, 1397, 1247 and 1298, with 9.86-, 9.79-, 8.73-, 8.66- and 8.16-fold increase compared to those without booster, respectively, indicating that boosting with XBB.1.5 subunit vaccines still induced strong antibody responses against JN.1 sublineages. However, JN.1 sublineages, including KP.2 and KP.3, revealed more than 2-fold decreases in neutralizing antibody titers compared to XBB.1.5, suggesting significantly enhanced neutralization evasion and the necessity of boosters based on JN.1, KP.2 or KP.3.